A conceptual space for episodic and semantic memory - Rubin, David C. (Memory & cognition, 2022)
I propose a model that places episodic, semantic, and other commonly studied forms of memory into the same conceptual space. The space is defined by three dimensions required for Tulving’s episodic and semantic memory. An implicit–explicit dimension contrasts both episodic and semantic memory with common forms of implicit memory. A self-reference dimension contrasts episodes that occurred to one person with semantic knowledge. A scene dimension contrasts episodes that occurred in specific contexts with context-free semantic information. The three dimensions are evaluated against existing behavioral and neural evidence to evaluate both the model and the concepts underlying the study of human memory. Unlike a hierarchy, which has properties specific to each category, the dimensions have properties that extend throughout the conceptual space. Thus, the properties apply to all forms of existing and yet-to-be-discovered memory within the space. Empty locations in the proposed space are filled with existing phenomena that lack a clear place in current theories of memory, including reports of episodic-like memories for events reported to but not witnessed by a person, fictional narrative accounts, déjà vu, and implicit components contributing to personality, the self, and autobiographical memory.